Islamistes et rebelles touaregs maliens : alliances, rivalités et ruptures - Emmanuel Grégoire (EchoGéo)
At the time when the conflict Malian seems to find a solution (June 2013), this article reconsiders alliances, competitions and ruptures between and within the various movements at the origin of the crisis. Inherent in their internal dynamics, the divisions partly explain why they recently failed on the political, military and religious levels. The author recalls the establishment of the Islamists in North Mali and examines their dissensions. He then analyses the claims and the divisions in the Tuareg movements, which radicalized since the preceding rebellions, as some decided Azawad be independent and while others (Anser ed-Dine) decided to set up an Islamic Tuareg state through armed conflict and to apply sharia. Lastly, he wonders why the Tuareg from Niger did not take up arms while the Malian and Nigeria Tuareg rebels show great similarities